Comparing the Boxgrove and Atapuerca (Sima de los Huesos) human fossils: Do they represent distinct paleodemes?. Issue 172 (November 2022) - Lockey, Annabelle L.; Rodríguez, Laura; Martín-Francés, Laura; Arsuaga, Juan Luis; Bermúdez de Castro, José María; Crété, Lucile; Martinón-Torres, María; Parfitt, Simon; Pope, Matt; Stringer, Chris
Abstract: The early Middle Pleistocene human material from Boxgrove (West Sussex, UK) consists of a partial left tibia and two lower incisors from a separate adult individual. These remains derive from deposits assigned to the MIS 13 interglacial at about 480 ka and have been referred to as Homo cf. heidelbergensis . The much larger skeletal sample from the Sima de los Huesos (Atapuerca, Spain) is dated to the succeeding MIS 12, at about 430 ka. This fossil material has previously been assigned to Homo heidelbergensis but is now placed within the Neanderthal clade. Because of the scarcity of human remains from the Middle Pleistocene and their morphological variability, this study assessed whether the Boxgrove specimens fit within the morphological variability of the homogeneous Sima de los Huesos population. Based on morphometric analyses performed against 22 lower incisors from Sima de los Huesos and published material, the data from the Boxgrove incisors place them comfortably within the range of Sima de los Huesos. Both assemblages present robust incisors distinct from the overall small recent Homo sapiens incisors, and Boxgrove also aligns closely with Homo neanderthalensis and some other European Middle Pleistocene hominins. Following morphological and cross-sectional analyses of the Boxgrove tibia compared to seven adult Sima de los Huesos specimens and a set of comparative tibiae, Boxgrove is shown to be similar to Sima de los Huesos and Neanderthals in having thick cortices and bone walls, but in contrast resembles modern humans in having a straight anterior tibial crest and a suggestion of a lateral concavity. Based on the patterns observed, there is no justification for assigning the Boxgrove and Sima de los Huesos incisors to distinct paleodemes, but the tibial data show greater contrasts and suggest that all three of these samples are unlikely to represent the same paleodeme.